2006
DOI: 10.1093/glycob/cwj085
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan oligosaccharides induce cell death through PI3-K/Akt pathway independently of NF-κB transcription factor

Abstract: Several studies indicate that hyaluronan oligosaccharides (oHA) are able to modulate growth and cell survival in solid tumors; however, no studies have been undertaken to analyze the effect of oHA on T-lymphoid disorders. In this work we showed that oHA were able to induce apoptosis in lymphoma cell lines. Since PI3-K/Akt and nuclear factor-kappaB (NF-kappaB) are major factors involved in cell survival and anti-apoptotic pathways in lymphoma cells, we hypothesized that oHA could induce apoptosis through inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…HA is reported to protect against apoptosis and to promote survival in various types of cells, including granulosa cells (44), articular chondrocytes (45,46), and human aortic smooth muscle cells (37). In contrast, other studies showed that HA treatment induces cell death in cultured human gingival fibroblasts (47) and lymphoma cell lines (48). Thus, the regulatory effect of HA upon cell viability appears to depend upon cell context, even when controlling for the size of HA, because high molecular weight HA has been shown to either promote cellular survival (37) or induce cell death (49) in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…HA is reported to protect against apoptosis and to promote survival in various types of cells, including granulosa cells (44), articular chondrocytes (45,46), and human aortic smooth muscle cells (37). In contrast, other studies showed that HA treatment induces cell death in cultured human gingival fibroblasts (47) and lymphoma cell lines (48). Thus, the regulatory effect of HA upon cell viability appears to depend upon cell context, even when controlling for the size of HA, because high molecular weight HA has been shown to either promote cellular survival (37) or induce cell death (49) in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with previous studies demonstrating that oHA induces apoptosis by suppressing the PI3K/Akt cell survival pathway. 15,21 This pathway appears to be critical for survival of multidrug resistant cells. Indeed, aberrantly activated PI3K/Akt pathway increases antiapoptotic signals, overwhelms proapoptotic signals of antineoplasic drugs and confers drug resistance limiting success of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…21 Briefly, oligosaccharides were obtained after enzymatic digestion of LMW-HA (5 mg/ml) with bovine testicular hyaluronidase (Hase) employing 500 U/mg of HA incubating at 37°C for 24 hr. The reaction was stopped by boiling for 5 min.…”
Section: Preparation Of Ohamentioning
confidence: 99%
See 1 more Smart Citation
“…induce cell death in lymphoma cells 35 and inhibit anchorage-independent growth in lung, mammary, and colon cancer cell lines through PI3K/Akt pathway in vitro. 14 The treatment of HA oligos reduces tumor volume in vivo in lung and breast cancers, 14 osteosarcoma, 20 and melanoma.…”
Section: Hyaluronan Oligosaccharides For Breast Cancermentioning
confidence: 99%